Where the wild things grow: an analysis of urban agriculture in U.S. cities - Jeffrey Crew, Nichola, author; Opp, Susan, advisor; Duffy, Robert, committee member; Saunders, Kyle, committee member; Seman, Michael, committee member (Colorado State University. Libraries, 2022)
Industrial agriculture produces approximately 24% of the global greenhouse gas emissions emitted annually and agricultural nonpoint source (NPS) pollution is a primary source of water quality degradation to inland and coastal waters, as well as a significant contributor to ground water pollution (EPA 2017; EPA 2022). In the wake of the COVID-19 pandemic in 2022, supermarket food prices have increased 8.6% in the United States and are expected to swell an additional 3 to 4% over the course of 2022 while producers' profit margins continue to grow, with net income increasing by 500% (USDA 2022). Food benefits distributed through the Federal Supplemental Nutrition Assistance Program (SNAP) were threatened with proposed cuts of $4.2 billion during the Trump administration. While the Trump administration's cuts were eventually blocked by Federal courts and the American Rescue Plan of 2021 invested $12 billion to fight hunger, increasing food prices and stagnant wages place a larger burden on lower economic classes, increasing food justice and food security concerns. It's clear that alternatives to the industrial agricultural system are direly needed, and they are indeed actively being sought, primarily at the local level. Urban agriculture (UA) presents a potential avenue forward, especially to address the social equity concerns inherent in the industrial agriculture system. However, the extant literature on the subject lacks external validity and a comprehensive index of what efforts cities are employing to combat hunger, inequity, and environmental issues. This dissertation establishes a catalog that demonstrates the wide array of the means by which U.S. cities are pursuing, attending to, and integrating UA, particularly within the context of sustainability goals; why cities vary in their approach to UA; and how this compares to our understanding of local level sustainability efforts in the extant sustainability literature. To explore these questions the first chapter of this dissertation provides a comprehensive discussion of the UA and sustainability policy context and literature. The second chapter presents an index of municipal programs and policies to examine cities' activities related to UA, with the goal of painting a detailed portrait of the UA landscape in large U.S. cities. With this additive index, UA initiatives are catalogued and U.S. cities with populations over 200,000 are ranked accordingly. The third chapter employs quantitative methods to examine why cities' approaches to UA vary and what factors help explain this variation. This study pays particular attention to eight independent variables related to political ideology, percentage of Hispanic residents, population size and change, median home value, median household incomes, the presence of land grant universities, and adult diabetes rates. Subsequently, the fourth chapter of this research will turn its attention to examining specific cities, for a more comprehensive and qualitative understanding of what initiatives and programs individual cities are engaging in order to provide a richer, more textural, and meticulous understanding of individual cases. Finally, the fifth chapter concludes this research by highlighting key findings and what they mean for current understandings of sustainability initiatives at the municipal level, in addition to avenues for future research. This research finds that cities are engaging in a wide variety of innovative urban agriculture programs and policies and a vast majority are doing so in the name of sustainability. Many of the same factors that influence the likelihood of a city's pursuit of traditional sustainability policies, such as larger population size, political ideology, and increased wealth, also influence city engagement with UA. However, percentage of Hispanic residents demonstrates an effect contrary to what we would expect in the context of the sustainability literature. Overall, it's clear population size has a dominant effect on how aggressively a city pursues UA. Additionally, the case studies in Chapter Four highlight the importance of a city's relationship with local food policy groups and how participatory a relationship the city and community share regarding UA matters. This research contributes to our understanding of UA in the context of sustainability by providing insights into city attitudes toward UA, cataloging pertinent programs and policies, and offering preliminary explanations as to why cities vary in their efforts. Future research can build upon the foundations this dissertation presents and explore more specific aspects to further the extant literature.
Keywords: sustainability; urban agriculture; U.S. cities; policy index